Off-label use of rilpivirine in combination with emtricitabine and tenofovir in HIV-1-infected pediatric patients: A multicenter study. Issue 24 (June 2016) - Falcon-Neyra, Lola; Palladino, Claudia; Navarro Gómez, María Luisa; Soler-Palacín, Pere; González-Tomé, María Isabel; De Ory, Santiago J.; Frick, Marie Antoinette; Fortuny, Clàudia; Noguera-Julian, Antoni; Moreno, Elena Bermúdez; Santos, Juan Luis; Olbrich, Peter; et al.
Abstract : Abstract: To assess the safety and efficacy of rilpivirine in combination with emtricitabine and tenofovir (RPV/FTC/TDF) as a once-daily single-tablet regimen (STR) in HIV-1-infected children and adolescents we performed a multicenter case series study of HIV-1-infected patients. Inclusion criteria were initiation of therapy with RPV/FTC/TDF before the age of 18. Patients were divided into undetectable viral load (uVL) group, HIV-1 RNA < 20 copies/mL on stable combined antiretroviral therapy (cART), and detectable viral load (dVL) group, HIV-1 RNA ≥ 20 copies/mL at RPV/FTC/TDF initiation. Patients were monitored from the date of RPV/FTC/TDF initiation until June 30, 2015, RPV/FTC/TDF discontinuation or failure to follow-up. Seventeen patients (8 in uVL and 9 in dVL group) with age between 11.6 and 17.6 were included. Reasons for switching were toxicity (n = 4) and simplification (n = 4) in uVL; viral failure (n = 8) and cART initiation (n = 1) in the dVL group. After a median follow-up of 90 (uVL) and 40 weeks (dVL), 7/8 (86%) patients maintained and 8/9 (89%) achieved and maintained HIV-1 suppression. Median CD4 count increased from 542 to 780/μL (uVL, P = 0.069) and 480 to 830/μL (dVL, P = 0.051). Five patients (2 in uVL and 3 in dVL) improved their immunological status from moderate to no immunosuppression. Serum lipid profiles improved in both groups; cholesterol dropped significantly in the dVL group ( P = 0.008). Grade 1 laboratory adverse events (AEs) were observed in 3 patients. No clinical AEs occurred. Adherence was complete in 9 patients (5 in uVL and 4 in dVL); 1 adolescent interrupted treatment. Once-daily STR with RPV/FTC/TDF may be a safe and effective choice in selected HIV-1-infected adolescents and children.